(untitled) (Journal of the College of Languages (JCL), 2025)
The current research addresses the epistolary style in Hebrew literature in the Enlightenment Era. The researcher addressed this style of writing in Abraham’s novel (the hypocrite) that has become as mailbox of all the novel’s characters. The novelist utilized these letters to present the secrets and thoughts of the characters as well as their feelings. Generally, this novel was composed entirely of letters that aimed at preparing the readers, who were living outside Israel, to comprehend the implicit meaning of the novel. The writer in his novel depicted the Jewish people in a particular time who characterized as a conservative community. He found out that letters werean appropriate means to uncover the thoughts of characters. Those letters revolved around (criticism, piece of advice, guidance, cheating, and conspiracy). Abraham Mapu put forward in-depth information through this type of writing. It was clearly observed that the main plot of the novel concentrated on letters which were taken as an approach to write this novel. הקדמה: רומן מכתבים הוא סוג ספרותי חשוב של הסופרים היהודים ביצירותיהם בתקופות שונות, וביחוד בתקופת ההשכלה. הסופרים היהודים בתקופה ההיא, השתמשו במכתביםכאמצעים חשובים להעברת רעיונותיהם לקורא היהודי. הם מצאו שתפקידם של המכתבים ביצירותיהם הייתה מועילה, דרך השפעתם בקורא היהודי שבגולה. אברהם מאפו השתמש במכתבים ברוב יצירותיו, אך בעיט צבוע, המכתבים היו מכסים את הרומן הזה. ורוב הידיעות והרעיונות של הרומן הועברו דרך המכתבים האלה. על כן ’’עיט צבוע’’ נחשב כתבת דואר של דמויותו. המכתבים היו הדרך הקלה של מאפו להעביר את מחשבתו המשכילית, והאמצע החשוב להסיר את המסכה מהחסידים שהיו עומדים בצד השני נגד המשכילים.